2021
DOI: 10.1159/000520572
|View full text |Cite
|
Sign up to set email alerts
|

Low Serological Prevalence of SARS-CoV-2 Antibodies in Cancer Patients at a German University Oncology Center

Abstract: Background Coronavirus disease 2019 (COVID-19) cases in Germany, as in most other places in Europe or worldwide, are still highly prevalent. Vaccination rates currently remain low, putting cancer patients at a continued risk of infection with SARS-CoV-2, while prevalence of SARS-CoV-2 antibodies among cancer patients in Germany remains essentially unknown. Methods Between August 2020 and February 2021, patients admitted to our hospital were prospectively enrolled in our COVID-19 biobank. Collected sera were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that antibody titers in patients with certain cancers, including but not limited to, advanced cancers and B cell hematological malignancies, are either absent or very low not only after SARS-CoV-2 infection, but also after SARS-CoV-2 vaccination (5,(7)(8)(9)(10)(11)(31)(32)(33)(34). In line with the major aim of this study, we identified a unique immune signature based on upregulated CRP, IL-15, IL-18, and PlGF that could be used to identify patients who did not sufficiently respond to vaccination with BNT162b2 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that antibody titers in patients with certain cancers, including but not limited to, advanced cancers and B cell hematological malignancies, are either absent or very low not only after SARS-CoV-2 infection, but also after SARS-CoV-2 vaccination (5,(7)(8)(9)(10)(11)(31)(32)(33)(34). In line with the major aim of this study, we identified a unique immune signature based on upregulated CRP, IL-15, IL-18, and PlGF that could be used to identify patients who did not sufficiently respond to vaccination with BNT162b2 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients with certain cancers, including but not limited to, advanced cancers and B cell haematological malignancies, develop low or even absent antibody titres not only after SARS-CoV-2 infection, but also after SARS-CoV-2 vaccination [5,[7][8][9][10][11][29][30][31][32]. In line with the major aim of this study, we identified a unique immune signature based on upregulated CRP, IL-15, IL-18, and PlGF can be used to identify patients who did not sufficiently respond to vaccination with BNT162b2 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it was also expected that perhaps the dysfunctional immune responses in cancer patients would render them more susceptible to SARS-CoV-2 infection, leading to high COVID-19 mortality rates [ 10 ]. Recent studies conducted in Japan and Germany suggest that SARS-CoV-2 seroprevalence was lower among cancer patients [ 11 , 12 ]. However, whether lower SARS-CoV-2 seroprevalence also holds true in the SSA cancer patient population, especially in the presence of HIV-1 infection, is not clear, although no increase in COVID-19 cases and deaths among cancer patients has been reported from SSA [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study in France reported similar SARS-CoV-2 seroprevalence between cancer patients and healthcare workers, whereas another study from Spain reported higher SARS-CoV-2 seroprevalence among cancer patients [ 20 , 21 ]. Moreover, several studies from Japan, Germany, and Italy reported lower seroprevalence of SARS-CoV-2 among cancer patients [ 11 , 12 , 22 ]. There are no studies on the seroprevalence of SARS-CoV-2 among cancer patients from SSA.…”
Section: Introductionmentioning
confidence: 99%